THE ROLE OF FOREIGN DIRECT INVESTMENT IN SUSTAINING CHINA’S ECONOMIC GROWTH - ANA-CRISTINA BÂLGĂR (Global Economic Observer, 2015)
n over three decades and a half of spectacular economic growth – starting in 1979 with the launch of reform processes and with the dynamic mutations from an autarchic to a global model – the introduction and implementation of the policies targeting the use and attraction of foreign direct investment (FDI) represented an exceptionally important stage in China’s history of international “openness,” playing an active role in the promotion, support and enhancement of its economic development. The aim of this article is to outline China’s sinuous investment path, from the autarchic pattern followed by the stage of economic openness characterised by the application of the “open doors” policy and up to the rethinking of the development paradigm and the country’s affirmation on the market as a new powerhouse in the global economy. Our research also aims to outline the implications that all these stages had on China’s current position of world leader in terms of inward FDI. As such, by means of comparative, quantitative and qualitative analyses, we will examine the evolution in time and the external impact of policies regarding the attraction of FDI, as well as the strategy aiming at incentivising Chinese outward investment – a relatively recent phenomenon – and the related support measures, in order to identify the country’s current development stage and its position in the global landscape, as well the possible challenges that China might face in the future.